Advances in Sulphonation Techniques Liquid Sulphur Dioxide as a Solvent of Sulphur Trioxide - Ashar, Navin G.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book presents a complete, in-depth analysis for on the impact of liquid sulfur dioxide and liquid sulfur trioxide to carry out complex and difficult sulfonations, as well as manufacture of sulfuric acid with a CAPEX requirement of less than half, an area requirement less than one-third, and no emission of sulfur dioxide. The processes described in this volume represents an innovative approach relevant to the current manufacturing processes of sulfuric acid, sulfamic acid, para toluene sulfonic acid and other sulfonated product.
Introduction -- Chemical and Physical Properties of Sulphur Dioxide and Sulphur Trioxide -- Manufacture of 25% & 65% Oleums as Well as Liquid Sulphur Trioxide -- Manufacture of Liquid Sulphur Dioxide -- World Production of Liquid SO2 and SO3 -- Techno Economic Evaluation of Processes Involved to Manufacture Liquid Sulphur Dioxide and Liquid Sulphur Trioxide -- Application of Sulphonation by Liquid SO3 Dissolved in Liquid SO2 -- Impact on the Future Processes for the Manufacture of Chemicals -- Case Studies and Its Commercial Application -- Summary -- Appendices.
Keywords: Chemistry, Technical; Inorganic chemistry; Manufactures; Security systems; Industrial Management; Industrial Chemistry; Inorganic Chemistry; Machines, Tools, Processes; Security Science and Technology; Industrial Management